The Role of Silicon in Higher Plants under Salinity and Drought Stress - Coskun, Devrim; Britto, Dev T.; Huynh, Wayne Q.; Kronzucker, Herbert J. (Frontiers in Plant Science, 2016)
Although deemed a “non-essential” mineral nutrient, silicon (Si) is clearly beneficial to plant growth and development, particularly under stress conditions, including salinity and drought. Here, we review recent research on the physiological, biochemical, and molecular mechanisms underlying Si-induced alleviation of osmotic and ionic stresses associated with salinity and drought. We distinguish between changes observed in the apoplast (i.e., suberization, lignification, and silicification of the extracellular matrix; transpirational bypass flow of solutes and water), and those of the symplast (i.e., transmembrane transport of solutes and water; gene expression; oxidative stress; metabolism), and discuss these features in the context of Si biogeochemistry and bioavailability in agricultural soils, evaluating the prospect of using Si fertilization to increase crop yield and stress tolerance under salinity and drought conditions.